New perspectives on endangered languages : bridging gaps between sociolinguistics, documentation and language revitalization - Flores Farfán, José Antonio; Ramallo, Fernando F. (Culture and language use, 2010)
Understanding sociolinguistics as a theoretical and methodological framework hopefully could attempt to promote change and social development in human communities. Yet it still presents important political, epistemological, methodological and theoretical challenges. A sociolinguistics of development, in which the revitalization of linguistic communities is the priority, opens new perspectives for the emerging field of linguistic documentation, in which the societal aspects of research, stressed by sociolinguistics, have frequently been marginal. The need to focus on the documentation of lingui.